If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -450 + -12y = -120 Solving -450 + -12y = -120 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '450' to each side of the equation. -450 + 450 + -12y = -120 + 450 Combine like terms: -450 + 450 = 0 0 + -12y = -120 + 450 -12y = -120 + 450 Combine like terms: -120 + 450 = 330 -12y = 330 Divide each side by '-12'. y = -27.5 Simplifying y = -27.5
| 390-12y=-120 | | 50-12y=-120 | | -20-12y=-210 | | 5x-4*6=39 | | -3x+7y=13 | | x*3+12+34=23 | | (3-x)5=3-2(2x-1) | | 4(n-5)+8(n+5)=0 | | 2(n+5)-3(n-5)=2(n-6)-8(n+8) | | 6(3n+2)-3(4n-5n)=10 | | 4(5n-4n)+3(4n-5n)-3(n+5)=15 | | 6n-12n+5=-10 | | 5n-100=-10 | | 7n+100=20 | | 13-[29]= | | 6n+87=-9 | | 3(5n-5)-4(3n+4)=100 | | 2(3n+5n)+3(4n+5)=15 | | 3*2-3(4-6)= | | 6n-12=100 | | -2*3+6(-4)= | | 5n+9=12 | | 8-6(2+4)= | | 4/7*21 | | (2+3)4= | | x^2+5x=42 | | 2[5-3(x+1)]=25+x | | x^2+y^2+2x-2y=0 | | x^2+y^2+2x-2y=11 | | -5(x+3)=7x+5 | | 2.899x=2.33x+100 | | 36m*60m= |